Richard Wright, Toni Morrison, and United States book clubs - Mark Madigan (Acta Neophilologica, 2004)
This essay focuses on the influence of commercial book clubs in the United States. It will examine the country's oldest commercial book club, the Book-of-the-Month Club (BOMC), Oprah's Book Club (OBC), which bears the name of its founder, television personality Oprah Winfrey, and their roles in the careers of two African-American authors, Richard Wright and Toni Morrison.